Development and Optimization of Naringenin-Loaded Chitosan-Coated Nanoemulsion for Topical Therapy in Wound Healing - Sabah H. Akrawi; Bapi Gorain; Anroop B. Nair; Hira Choudhury; Manisha Pandey; Jigar N. Shah; Katharigatta N. Venugopala (MDPI AG, 2020)
The potential role of naringenin (NAR), a natural flavonoid, in the treatment of chronic wound has prompted the present research to deliver the drug in nanoemulsion (NE) form, where synergistic role of chitosan was achieved through development of chitosan-coated NAR NE (CNNE). The NE consisted of Capryol 90, Tween 20 and Transcutol P, which was fabricated by low-energy emulsification method to encapsulate NAR within the oil core. The optimization of the formulated NEs was performed using Box-Behnken statistical design to obtain crucial variable parameters that influence globule size, size distribution and surface charge. Finally, the optimized formulation was coated with different concentrations of chitosan and subsequently characterized in vitro. The size of the CNNE was found to be increased when the drug-loaded formulation was coated with chitosan. Controlled release characteristics depicted 67-81% release of NAR from the CNNE, compared to 89% from the NE formulation. Cytotoxicity study of the formulation was performed in vitro using fibroblast cell line (NIH-3T3), where no inhibition in proliferation of the cells was observed with CNNE. Finally, the wound healing potential of the CNNE was evaluated in an abrasion-created wound model in experimental animals where the animals were treated and compared histologically at 0 and 14 days. Significant improvement in construction of the abrasion wound was observed when the animals were treated with formulated CNNE, whereas stimulation of skin regeneration was depicted in the histological examination. Therefore, it could be summarized that the chitosan coating of the developed NAR NE is a potential platform to accelerate healing of wounds.